Efektivitas Strategi Know Want Learned (KWL) dalam Meningkatkan Keterampilan Berbicara Bahasa Jepang - Setiawati, Nia; Nur Wijayanti, Rahmania; Fitri Asih, Nur Saadah (Chi'e: Journal of Japanese Learning and Teaching, 2021)
This research was conducted to attempt at improving Japanese Speaking skill through Know Want Learned (KWL) strategy of the 2018-2019’s academic years students of Japanese Department, Faculty of Language and Literature of State University of Jakarta. The classroom experiment study was triggered by the fact that the subjects still faced problem in Japanese speaking skill. The classroom action study made use of pre-test and post-test research design with quantitative analysis. Based on the experiment result, the data administered showed that there was improvement in the students’ Japanese speaking skill. Before giving the treatment, the classes’ average of pretest was 68.2. After implementing the KWL strategy, the classes’ average of posttest was 80.3. This indicated that the students’ Japanese speaking skill has improved. Moreover, the hypothesis test revealed tcalculate is higher than ttable. Therefore, these findings clearly suggested that improving Japanese speaking skill through KWL strategy was highly effective.